Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-12-20T11:04:10+01:00
Oblicz W+Q, W-Q, Q*W, 3Q-2W
a)W(x)=x³-x²+6x-6 Q(x)=2x²-3

W+Q = x³-x²+6x-6+2x²-3 =x³+x²+6x-9
W-Q = x³-x²+6x-6-2x²+3 =x³-3x²+6x-3
W*Q =( x³-x²+6x-6)*(2x²-3) = 2x^5-2x^4+12x³-12x²-3x³+3x²-18x+18=2x^5 -2x^4 +9x³-9x²-18x+18
3Q-2W =3(2x²-3)-2( x³-x²+6x-6)= 6x²-9 - 2x³+2x²-12x+12=-2x³+8x²-12x+3

b)W(x)=3x³+2x²+1 Q(x)=-2x³+x-3
W+Q = 3x³+2x²+1+(-2x³+x-3)=x³+2x²+x-2
W-Q = 3x³+2x²+1 -(-2x³+x-3)= 5x³+2x²-x+4
W*Q = (3x³+2x²+1)*(-2x³+x-3)= 6x^6 -4x^5-2x³+3x^4 + 2x³+x-9x³-6x²-3=6x^6 -4x^5 +3x^4 -9x³-6x²+x-3
3Q-2W = 3(-2x³+x-3) - 2(3x³+2x²+1)= -6x³+3x-x-3 - 6x³-4x²-2=-12x³-4x²+2x-5